COVID‐19: A Greek Perspective. Issue 5 (28th September 2020) - Iliopoulos, Dimitrios C.
Abstract: Greece has managed to timely and properly implement a public health safety plan and contained the burden of the coronavirus disease (COVID‐19) pandemic. On the contrary, COVID‐19 has led to a national catastrophe in countries with superior infrastructures, such as Italy, Spain, France, and the United States. At a time when our nation's healthcare resources were insufficient to meet this unprecedented demand, it was necessary to prioritize needs in the hopes of maximizing lives saved. Although delaying definitive treatment of disorders presented a risk to specific individuals, countless others afforded life‐saving resources necessary to overcome the most threatening manifestation of this illness. The cataclysm of COVID‐19 offered an opportunity to reshape health care in ways that may not have seemed possible just a few months ago. To help scientists and clinicians across disciplines connect their strengths, so that together we can advance the state of the art in medicine and lead the way to a new era of computational medicine.